The transcriptional profile of coronary arteritis in Kawasaki disease. (December 2015) - Rowley, Anne; Wylie, Kristine; Kim, Kwang-Youn; Pink, Adam; Yang, Amy; Reindel, Rebecca; Baker, Susan; Shulman, Stanford; Orenstein, Jan; Lingen, Mark; Weinstock, George; Wylie, Todd
Abstract Background Kawasaki Disease (KD) can cause potentially life-threatening coronary arteritis in young children, and has a likely infectious etiology. Transcriptome profiling is a powerful approach to investigate gene expression in diseased tissues. RNA sequencing of KD coronary arteries could elucidate the etiology and the host response, with the potential to improve KD diagnosis and/or treatment. Methods Deep RNA sequencing was performed on KD (n = 8) and childhood control (n = 7) coronary artery tissues, revealing 1074 differentially expressed mRNAs. Non-human RNA sequences were subjected to a microbial discovery bioinformatics platform, and microbial sequences were analyzed by Metastats for association with KD. Results T lymphocyte activation, antigen presentation, immunoglobulin production, and type I interferon response were significantly upregulated in KD arteritis, while the tumor necrosis factor α pathway was not differentially expressed. Transcripts from known infectious agents were not specifically associated with KD coronary arteritis. Conclusions The immune transcriptional profile in KD coronary artery tissues has features of an antiviral immune response such as activated cytotoxic T lymphocyte and type I interferon-induced gene upregulation. These results provide new insights into the pathogenesis of KD arteritis that can guide selection of new immunomodulatory therapies for high-risk KD patients, and provide direction for future etiologic studies.